1991
DOI: 10.1029/91jc00641
|View full text |Cite
|
Sign up to set email alerts
|

Currents and water masses of the Coastal Transition Zone off northern California, June to August 1988

Abstract: In summer 1988, we made repeated mesoscale surveys of a grid extending 200 km offshore between 37°N and 39°N in the coastal transition zone off northern California, obtaining continuous acoustic Doppler current profiler data and conductivity‐temperature‐depth data at standard stations 25 km apart on alongshore sections 40 km apart. All surveys showed a baroclinic equatorward jet, with core velocities of >50 cm s−1 at the surface decreasing to about 10 cm s−1 at 200 m, a width of 50–75 km, and a baroclinic tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(43 citation statements)
references
References 35 publications
4
38
1
Order By: Relevance
“…These sites have been previously recognized as hot spots for eddy generation [Chaigneau et al, 2009;Kurian et al, 2011]. The observed negative S 0 (Figure 8c) is probably due to the local eddy-induced downwelling of the surface layers composed of fresh Pacific Subarctic Water [Simpson et al, 1984;Emery and Meincke, 1986;Huyer et al, 1991;Checkley and Barth, 2009;Dong et al, 2012] that can be clearly identified in Figure 9a (color shading). The temporal evolution of the corresponding composite anomalies is consistent with their mean profiles and their intensity does not present strong variations between the growth, mature and decay phases (Figures 10a-10c).…”
Section: California Upwelling System (Calus)mentioning
confidence: 82%
See 1 more Smart Citation
“…These sites have been previously recognized as hot spots for eddy generation [Chaigneau et al, 2009;Kurian et al, 2011]. The observed negative S 0 (Figure 8c) is probably due to the local eddy-induced downwelling of the surface layers composed of fresh Pacific Subarctic Water [Simpson et al, 1984;Emery and Meincke, 1986;Huyer et al, 1991;Checkley and Barth, 2009;Dong et al, 2012] that can be clearly identified in Figure 9a (color shading). The temporal evolution of the corresponding composite anomalies is consistent with their mean profiles and their intensity does not present strong variations between the growth, mature and decay phases (Figures 10a-10c).…”
Section: California Upwelling System (Calus)mentioning
confidence: 82%
“…by the California Current [Simpson et al, 1984;Emery and Meincke, 1986;Huyer et al, 1991;Checkley and Barth, 2009;Dong et al, 2012]. Both the shoaling of the isopycnals associated with these surface-intensified eddies and the advection of saltier near-coastal water across fresher offshore waters can lead to this observed positive S 0 .…”
Section: 1002/2015jc010950mentioning
confidence: 98%
“…The onset of upwelling (spring through late summer) differs annually, and is marked by the 'spring transition' (Huyer et al 1990), when sea-surface temperatures drop abruptly in association with a sudden strengthening of the northwest wind (Breaker & Mooers 1986). This equatorward wind stress, in combination with Earth's rotation, leads to the offshore transport of surface water (Ekman transport).…”
Section: Introductionmentioning
confidence: 99%
“…The southward jets separate nutrient-rich upwelled waters from the relatively barren offshore waters (e.g., Huyer et al, 1991). The core of the offshore California Current flow is located approximately 250−350 km from the coast at the border of Oregon and California and is about 300 km from the coast at Point Conception (~35°N; Hickey, 1979;Lynn and Simpson, 1987).…”
Section: Dynamics Of the California Currentmentioning
confidence: 99%